Designing learning tools by using problem based instruction model on science integrated to character education - Estuhono Estuhono; Joni Afriko (Fakultas Ilmu Pendidikan UNP)
The integrating of character values into science learning tools should be able to build character for the students. The purpose of this research is to design science learning tools by using problem based instruction model on science for elementary school that is integrated by education character values. The research was Research and Development. The Learning tools were developed by using 4-D model (Define, Design, Develop and Disseminate). In the define phase, there is curriculum analysis, students analysis and analysis of the material. Design phase is to design science learning tools by using problem based instruction model that is integrated by education character values, develop phase is to develop innovative science learning tools by using problem based instruction model and disseminate phase is to spread science learning tools by using problem based instruction model that is integrated by education character values. The data are collected by using a validation sheet of learning tools, practicality questionnaires and instrument of effectiveness. However, this research is still at the design stage. Based on analysis curriculum got, curriculum at elementary school is still applying KTSP. Then based on analysis of students, it reveals that the students of elementary school are at the stage of concrete operations. Then, the material, it shows facts, concepts, principles and procedures that integrate the character values of education. The results of the Design stage, reveals that syllabus, lesson plan, worksheet, assessment designed following the steps of PBI model integrated by character education.